booleanlogicboolean-expressionboolean-algebra

How do I create a simplified logic circuit of this given [(A’B’)’ + (A’+ B’)’]’ ? and What is the simplified Boolean expression?


I have to draw the simplified logic circuit of this given [(A’B’)’ + (A’+ B’)’]’ and also get the simplified boolean expression


Solution

  • From DeMorgan Theory

         ((A'B')' + (A'+ B')')'=(A+B + AB)'   
         (A+B + AB)'   = (A+B)'. (AB)'
         (A+B)'. (AB)' = (A'.B') .(A'+B')
    

    assume

    X=A' ,Y=B'
    

    we can conclude that

    (XY)(X+Y) is (XY)  
    

    as both (XY) and (X+Y) has to be 1 to produce 1 at output as seen from truth table of (XY)(X+Y) is (XY) is identical to XY

    enter image description here

    so as final result

    ((A'B')' + (A'+ B')')'=(A+B + AB)'  
    
    (A+B + AB)'   = (A+B)'. (AB)'
    
    (A+B)'. (AB)' = (A'.B') .(A'+B') = A'B'
    

    before simplifying

    enter image description here

    after simplifying

    enter image description here

    comparing outputs to make sure

    enter image description here